TINJAUAN YURIDIS TENTANG PELAKSANAAN HAK DAN KEWAJIBAN BADAN PENYELENGGARAAN JAMINAN SOSIAL MENURUT UNDANG-UNDANG NOMOR 24 TAHUN 2011 - Marsidah, Marsidah (Solusi, 2019)
The purpose of this study was to determine the rights and obligations of the Social Security Organizing Agency. The type of research used is the type of normative legal research and the data source used is a secondary data source. The rights and obligations of the Social Security Organizing Body are regulated in the provisions of articles 12 and 13 of Law Number 24 of 2011. The right of the Social Security Organizing Body is to obtain operational funds for the operation of programs sourced from social security funds and / or other sources in accordance with statutory provisions -invitation. Whereas the obligation of the Social Security Organizing Body is to provide a single identity number to the participant, that is, a number given specifically by the Social Security Organizing Board to each participant to ensure orderly administration of the rights and obligations of each participant. Information on the performance and financial condition of the Social Security Organizing Agency includes information on the amount of assets and liabilities, receipts and disbursements for each Social Security Fund and / or the total assets and liabilities, receipts and disbursements of the Social Security Organizing Body, providing benefits to all participants in accordance with the Law - Law on the National Social Security System, providing information to participants about the rights and obligations to follow applicable regulations, providing information to participants about the procedure for obtaining rights and fulfilling their obligations, providing information to participants about balances.